Gelae parile - Majka, Christopher; Langor, David (Zenodo, 2008)
Gelae parile (Fall, 1934) NEWFOUNDLAND: Spruce Brook, 9.VII.1949, E. Palmen, (2, MZHF). NOVA SCOTIA: Inverness Co.: Lone Shieling, Cape Breton Highlands National Park, vii.1983, R. Vockeroth, malaise trap, (2, CNC); MacKenzies Mtn., Cape Breton Highlands National Park, 11-18.VII.1983, R. Vockeroth, pan trap, (2, CNC); Queens Co.: Medway River, 13.VII.1993, J and T. Cook, car net, (2, JCC). Gelae parile is newly recorded in Newfoundland, Nova Scotia, and in Atlantic Canada as a whole (Fig. 7). It was collected in hemlock, pine, aspen, fir, maple, and other forests from a variety of litter sources such as rotting stumps, and leaf litter. There are host records from the slime molds Cribraria sp. and Dictydium cancellatum (Batch) McBride (Miller and Wheeler 2004). Published as part of Majka, Christopher & Langor, David, 2008, The Leiodidae (Coleoptera) of Atlantic Canada: new records, faunal composition, and zoogeography, pp. 357-402 in ZooKeys 2 (2) on page 382, DOI:10.3897/zookeys.2.56, http://zenodo.org/record/576397